Analysis of Road Traffic Crashes Data of Perak State in Malaysia - Abd Rahman, Raha; Hussein, M M H Meor; Mohd Saim, Nur Amylia Izrin; Megat Tajuddin, Megat Zuhairy (International Journal of Sustainable Construction Engineering and Technology, 2023)
Road traffic accidents are one of Malaysia’s top five major causes of death and is one of the most critical public health concerns in 2023. As a result, this article offers research based on data from different Malaysian government organisations and analysing the changes in the pattern of Road Traffic Crashes (RTC) in Perak, Malaysia. From 2011 to 2018, data was analysed based on road traffic collisions and categories of casualties concerning gender, age, types of roads and vehicles, and road users. The mortality and injury rates per 100,000 people were used to calculate performance for road safety. It was found that with a 0.59% increase in Perak’s population and an increase in the number of cars, there are 30,669 total crashes and 491 road deaths in 2020. Furthermore, this study discovered that motorcycles were the most common vehicle involved in road traffic deaths from 2011 to 2018, which should raise concerns since motorbikes have become an essential mode of transportation. In Perak, most road deaths were males between the ages of 16 and 20. Finally, this study discovered that the death and injury rates per 100,000 people in Perak are 19.56 and 75.82, respectively, indicating that the fatality rate is dropping, but the injury rate increased dramatically in 2020 compared to 2019. The Perak state administration must investigate why the situation has worsen after a decade. Somehow or rather, the state must address this issue, and it is advised that further research be conducted to identify mechanisms to enhance the current scenario to lower the number of RTCs, notably deaths, in the state.